2016
DOI: 10.1158/1538-7445.sabcs15-p5-17-03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-17-03: The 12-gene DCIS score assay: Impact on radiation treatment (XRT) recommendations and clinical utility

Abstract: Background: In the management of DCIS clinicians and patients (pts) must choose between the various options for breast conservation treatment based on an assessment of local recurrence (LR) risk. Traditional clinicopathologic (CP) factors such as age, size, grade, margin width or comedo necrosis, provide an average LR risk derived from clinical trials and population studies. The Oncotype DX® 12-gene assay for DCIS gives individual 10-yr LR risk estimates and has now been validated in two studies in a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Further validation in a similar Ontario-based population of 718 patients supported the value of DS as an independent predictor of risk of local recurrence [106]. Two recent US-based multi-institutional clinical utility studies have shown that application of DS has led to significant changes in treatment recommendations, suggesting that clinicians are considering the information provided by the test in their decision-making process [107,108].…”
Section: Challenges In the Management Of Dcis: The Need For Predictivmentioning
confidence: 88%
“…Further validation in a similar Ontario-based population of 718 patients supported the value of DS as an independent predictor of risk of local recurrence [106]. Two recent US-based multi-institutional clinical utility studies have shown that application of DS has led to significant changes in treatment recommendations, suggesting that clinicians are considering the information provided by the test in their decision-making process [107,108].…”
Section: Challenges In the Management Of Dcis: The Need For Predictivmentioning
confidence: 88%
“…69,70 Two recent studies suggest that the Oncotype DX Breast DCIS assay has already led to a significant reduction in radiotherapy recommendations by surgeons and radiation oncologists. 71,72 A few limitations of the Oncotype DX Breast DCIS Score should be noted. One major limitation is expense; a recent cost-benefit analysis revealed that although incorporation of the Oncotype DCIS Score decreases the proportion of women undergoing radiotherapy per recurrence event prevented, these strategies were not cost-effective.…”
Section: Gene Expressionmentioning
confidence: 99%